Distinct gene mutation profiles among multiple and single primary lung adenocarcinoma - Wang, Yadong; Wang, Guanghui; Zheng, Haotian; Liu, Jichang; Ma, Guoyuan; Huang, Gemu; Song, Qingtao; Du, Jiajun (Frontiers in Oncology, 2022)
With the development of technologies, multiple primary lung cancer (MPLC) has been detected more frequently. Although large-scale genomics studies have made significant progress, the aberrant gene mutation in MPLC is largely unclear. In this study, 141 and 44 lesions from single and multiple primary lung adenocarcinoma (SP- and MP-LUAD) were analyzed. DNA and RNA were extracted from formalin-fixed, paraffin-embedded tumor tissue and sequenced by using the next-generation sequencing-based YuanSu450TM gene panel. We systematically analyzed the clinical features and gene mutations of these lesions, and found that there were six genes differently mutated in MP-LUAD and SP-LUAD lesions, including RBM10, CDK4, ATRX, NTRK1, PREX2, SS18. Data from the cBioPortal database indicated that mutation of these genes was related to some clinical characteristics, such as TMB, tumor type, et al. Besides, heterogeneity analysis suggested that different lesions could be tracked back to monophyletic relationships. We compared the mutation landscape of MP-LUAD and SP-LUAD and identified six differentially mutated genes (RBM10, CDK4, ATRX, NTRK1, PREX2, SS18), and certain SNV loci in TP53 and EGFR which might play key roles in lineage decomposition in multifocal samples. These findings may provide insight into personalized prognosis prediction and new therapies for MP-LUAD patients.